Scope, timing and strategic adjustment in emerging markets: Manufacturer strategies and the case of MRI - Teplensky, Jill D.; Kimberly, John R.; Hillman, Alan L.; Schwartz, J. Sanford (Strategic Management Journal, 1993)
Abstract This study examines the realized strategies of all domestic manufacturers in a growing, high technology, industrial market characterized by high levels of regulatory, demand, and technological uncertainty. These manufacturers have behaved quite differently and experienced varying levels of success in the market. A typology of entry strategies grounded in an intensive analysis of these data is presented. Specifically, it addresses the timing and scope of a firm's entry into the market, strategic adjustments over time, and the impact of these decisions on the firm's performance. It is proposed that these strategies represent trade‐offs between the risks of resource commitment and competitive preemption. Specific, testable hypotheses based on this typology are also provided.